Pengaruh kualitas produk, harga, dan citra merek terhadap keputusan pembelian Wardah kosmetik - Rohmah, Ziadatur; Sukaris, Sukaris (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
The rapid expansion of the economy and the emergence of multinational firms have intensified competition in the cosmetics industry, especially in the beauty goods market, which poses a significant challenge to this subject. Client choice is becoming more important while selecting cosmetic products due to the expanding quantity of firms and product possibilities. The purpose of this study is to analyze Wardah Cosmetics' purchase decisions in relation to product quality, price, and brand image. This is important for understanding the industry's competitive landscape and how customers make purchasing decisions. Using the Accidental Non Probability Sampling approach, 105 female students from Muhammadiyah Gresik who had purchased Wardah cosmetics were selected as the sample for this study. It was also decided to use simple linear regression analysis as the study technique. According to the study's results, consumers' purchasing decisions are heavily influenced by Wardah cosmetics' quality, price, and brand image.